An Analytical Review of the Values in Adabul Islam fi Nidzomil Usroh: Early Marriage as a Preventive Measure Against Adultery and a Means of Adolescent Maturation - Aswat, Hazarul; Zako, Mushthafa Hilmiy Ar Rasyiid (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
Marriage is the union of a man and a woman who are not mahram (unmarriageable kin). Early marriage refers to the marriage of a man and a woman who are still considered young in age. This study is prompted by the concerning situation in Indonesia today, where many young people have fallen into acts of fornication. Test results show that many young women are no longer virgins and that a significant number have become pregnant outside of marriage. This study seeks to explore one possible solution to the issue of fornication by referring to Islamic teachings, specifically through the book authored by Abuya Prof. Dr. As-Sayyid Muhammad bin As-Sayyid Alwi Al-Maliki Al-Hasani Ra, who is more commonly known as Abuya Maliki Ra. This study employs a qualitative research method, specifically a type of library research. Data collection is carried out by identifying key points relevant to the main issue, followed by analysis of the findings through translation and interpretation. The results are then presented in a discussion that relates directly to the core problem. First, Abuya Maliki wrote this book in response to the various problems occurring within marriage. Second, he structured the book in stages that are easy to understand, explaining each issue individually along with its solution. Third, Abuya Maliki authored the book because the problems addressed in the study had already existed, and have now become even more serious-like a dangerous virus attacking the human body. This study is expected to provide a deeper understanding of the importance of encouraging early marriage, in order to prevent acts of fornication within society.